Socio-technical innovation bundles (STIBs) and their impacts on women’s empowerment and resilience - Awinoh, Martha; Ngugi, Elphas (CGIAR, 2024)
Eileen Nchanji, co-lead of HER+ EMPOWER work package highlights STIBs can encompass a range of initiatives that integrate both technological solutions and social interventions to promote gender equality, enhance women's agency, and build resilience in the face of socio-economic and environmental challenges.